Creative Teaching Strategies Implemented in Teaching English to Young Language Learner - Nilma Taula’bi’ (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2022)
This research objective is to find out the creative teaching strategies implemented in teaching English to Young Language Learner. The method used in this research is qualitative research method. The participant is the teachers and young language learners or the children in Sunday School Jemaat Buntu Pasele Rantepao. The instruments used to collect the data are interview and observation. The data analyzes by Miles and Huberman theory. The creative teaching strategies implemented in teaching English to Young Language Learner at English tuition class at Sunday School Jemaat Buntu Pasele Rantepao are (1) Play games: memory games, Hangman, Simon Says and board games. (2) Use storytelling. (3) Use music and songs. (4) Used technology such as educational apps, videos, and interactive games to teach English vocabulary and grammar. (5) Make it interactive: role-plays, group discussions, and other activities that require the children to use English. The last is Sunday Meeting in the tourist object.